KEANEKARAGAMAN JENIS BURUNG DI KAWASAN PENYANGGA TAMAN HUTAN RAYA SULTAN SYARIF HASYIM PROVINSI RIAU - Hutapea, Andriano; Suwarno, Eno; Hadinoto, Hadinoto (Wahana Forestra: Jurnal Kehutanan, 2019)
The existence and spread of birds are closely related to the availability of food and habitat for birds while showing the existence of an individual or group of individuals. Species of birds and how the spread of bird species is based on habitat in the buffer zone of Tahura Sultan Syarif Hasyim. The method used is to use the Point Count method while calculating existing vegetation using anveg (vegetation analysis). The composition of birds in various vegetation cover is divided into 2 namely secondary forest and agroforestry land, in secondary forests there are 292 individuals, 41 species, 25 families from 9 orders while on agroforestry land there are 213 individuals, 25 species, 16 families of 6 orders. Thus, in the buffer zone of Tahura Sultan Syarif Hasyim, there were 505 individuals, 48 ​​species, 28 families of 10 orders with diversity included in the category of "High Diversity" with a value of 3.54, in the distribution of 14 species of land species, 27 types of lower canopy, 37 types of middle canopy and 26 types of top canopy.